Ti2AlN MAX phase as a modifier of cellulose acetate membrane for improving antifouling and permeability properties - Mehrabani, Seyed Ali Naziri; Keskin, Basak; Arefi-Oskoui, Samira; Koyuncu, Ismail; Vatanpour, Vahid; Orooji, Yasin; Khataee, Alireza (Elsevier Sci Ltd, 2022)
The development of novel materials for the modification of filtration membranes is necessary to enhance their performance. In this study, the application of MAX phase-based material in the modification of cellulose acetate (CA) ultrafiltration membrane is reported to improve hydrophilicity, permeability, dye rejection and antifouling properties. Firstly, the Ti2AlN MAX phase was synthesized and exfoliated under ultrasonic to obtain nanosheets with an average width of 35 nm. Then, the influence of the prepared MAX phase on the CA membrane per-formance was assessed by blending different concentrations of it (0-1 wt%). The flux of pure water and bovine serum albumin protein solution was improved 27.5 % and 37.5 % by blending 0.5 wt% of the MAX phase into the matrix of the membrane. Moreover, the 0.5 wt% MAX/CA nanocomposite membrane represented ameliorated antifouling property with a flux recovery ratio of 86.3 %. This study showed that the MAX phase could be considered propitious additives to modify polymeric membrane performance.
Keywords: Ultrafiltration; Cellulose acetate; Protein separation; Antifouling; MAX phases